2019
DOI: 10.1615/int.j.uncertaintyquantification.2018025234
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Performance of Leja and Clenshaw-Curtis Collocation for Computational Electromagnetics With Random Input Data

Abstract: We consider the problem of quantifying uncertainty regarding the output of an electromagnetic field problem in the presence of a large number of uncertain input parameters. In order to reduce the growth in complexity with the number of dimensions, we employ a dimensionadaptive stochastic collocation method based on nested univariate nodes. We examine the accuracy and performance of collocation schemes based on Clenshaw-Curtis and Leja rules, for the cases of uniform and bounded, non-uniform random inputs, resp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…We apply the methods for yield estimation and optimization discussed in the previous sections to a benchmark problem in the context of electromagnetic field simulation. In particular, we employ the model of a rectangular waveguide with a dielectric inset, similarly to the one used in [36]. This model is well suited for validation purposes, as a closedform solution is available [37].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We apply the methods for yield estimation and optimization discussed in the previous sections to a benchmark problem in the context of electromagnetic field simulation. In particular, we employ the model of a rectangular waveguide with a dielectric inset, similarly to the one used in [36]. This model is well suited for validation purposes, as a closedform solution is available [37].…”
Section: Numerical Resultsmentioning
confidence: 99%
“…We will base the adaptive construction of anisotropic sparse interpolations on the dimension-adaptive algorithm first presented in [47] for quadrature purposes. Variants of this algorithm appear in a number of later works [16,30,36,37,48]. In this work, we assume the all underlying univariate interpolation rules employ Leja nodes, presented in Section 2.3, along with the level-to-nodes function m(i) = i + 1.…”
Section: Adaptive Anisotropic Leja Interpolationmentioning
confidence: 99%
“…Moreover, it was found to have a clear edge over the well-established LAR-gPC method. [37] and with a degree-adaptive LAR-gPC algorithm [9,50]. The size of the validation sample is Q = 10 5 .…”
Section: Meromorphic Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of domains have seen application of such dimension-adaptive samplers, e.g. computational electromagnetism [25], finance [21,16] or natural convection problems [13], to name just a few. We only perform a limited validation study, by examining the ability of the predicted output distribution to envelop the observed COVID-19 death count, conditional on a predefined intervention scenario.…”
Section: Introductionmentioning
confidence: 99%